(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2019)
Introduction: Pleural effusion is a common clinical manifestation of varying aetiology. Its outcome varies according to underlying aetiology. The causes and prognosis vary between developed and developing countries. Objectives: To find out the most common causes of pleural effusion in a tertiary care hospital of Bangladesh. Materials and Methods: Total 50 patients were enrolled in the study during the period from January 2014 to November 2015 in combined military hospital, Dhaka. Informed written consent was obtained from all patients under the study, explaining the risk benefits and objectives of the study before sampling. Data were collected using a structured questionnaire containing all the key variables along with radiological, laboratory and pleural fluid analysis report. Data presented as frequency and percentage and Chai-square test was performed by using SPSS 23.0. Results: Patients’ mean age was 48.28 ± 12.53 years and ranged from 12 to 70 years where half of them were above 50. Male-female ratio was 1.63:1. Sixty five percent of the patients had positive smoking history. Persistent cough, fever and weight loss were the main presenting symptoms. Radiological findings revealed 50% had isolated right-sided pleural effusion and laboratory investigation found 28% cases ESR value 50-100 mm in 1st hour. Pleural fluid examination revealed 75% patient had straw coloured pleural fluid. Sputum for Acid-Fast Bacilli and other relevant investigations revealed 44% patients had tuberculosis, 16% had pneumonia, 8% had malignancy and 24% had other causes of pleural effusion. Conclusion: This study revealed that the tuberculosis is the predominant cause of pleural effusion followed by pneumonia and malignancy. Journal of Armed Forces Medical College Bangladesh Vol.13(2) 2017: 15-17